EFEKTIVITAS MEDIA SOSIAL INSTAGRAM @LOKER_KOTASURABAYA DALAM PEMENUHAN KEBUTUHAN INFORMASI LOWONGAN PEKERJAAN DI SURABAYA - Erfianah, Milani Eka; Huda, Anam Miftakhul (The Commercium, 2022)
This research is entitled "Effectiveness of Instagram @loker_kotasurabaya Social Media in Fulfilling Job Vacancies Information Needs in Surabaya". A study of the effectiveness of social media using Uses and Gratification Theory which is also to find out the gap between the amount of desire sought and the reality obtained. The theory that is considered relevant in this research is Uses and Gratification, where media users have an active right to choose what media is able to meet their needs. Determination of the sample using a random sampling technique from the population of followers of the Instagram account @loker_kotasurabaya. Data was collected using a survey method, namely by distributing questionnaires. While the data analysis was carried out through gap analysis, analysis of TCR values, hypothesis testing by calculating t-count and t-table which resulted in Ho being rejected, Ha accepted. Because, t-count = 0.04243 is smaller than t-table = 0.1166. And from the results of the TCR analysis, the Instagram account @loker_kotasurabaya is very effective in meeting the information needs of followers. The research indicators are Information with Accurate, Timely, Relevant, Complete markers measured in the Gratification Sought and Gratification Obtained Dimensions indicating the Very Effective category. With a percentage of the TCR Gratification Sought Value / Desire Wanted with a percentage of 92%. Meanwhile, at the Gratification Obtained level, the Information indicator gets a percentage of 87%. Keywords : Instagram Effectiveness, Uses and Gratification Theory, Gaps